The Relationship Between Achievement Emotions and Engagement Among EFL Learners in the Post-Pandemic Era - Kuncoro, Adhityo; Anam, Syafi’ul; Wardhani, Dyah Rhetno (IJLECR (International Journal of Language Education and Cultural Review), 2024)
Investigating students’ perceptions of English learning is a topic that has received a lot of attention in the field of language education. The purpose of this study is to investigate the relationship between students’ achievement emotions (enjoyment and anxiety) and their engagement in the post pandemic era. 30 participants are selected from two different classes in the informatics engineering department. This study used a quantitative approach to examine the relationship between students’ achievement emotions and engagement levels. Data were collected through a Google Forms questionnaire, consisting of 19 items from the Foreign Language Enjoyment Scale (FLES), 8 items from the Foreign Language Classroom Anxiety Scale (FLCAS), and 15 items adapted from the Online English Learning Engagement (OELE) questionnaire, all measured with a five-point Likert scale. Descriptive analysis was conducted to summarize the data, and the results were analyzed using SPSS 27 to explore the relationships between emotions and engagement. The findings showed that (1) students’ enjoyment variable had significant effect towards students’ engagement (Sig. 0,001<0,05). Students’ enjoyment had positive correlation while students’ anxiety had negative correlation towards students’ engagement variable. (2) students’ enjoyment, specifically personal enjoyment had significant effect on students’ engagement. The conclusion is that educators recommend being more aware of their students’ emotional states; considering enjoyment has important roles in language education, students’ feelings of enjoyment should be increased, which may reduce degrees of apprehension and result in better language learning. An investigation of multimodal integration to reduce students’ anxiety could be a suggestion for the next research.